Investigating the Semantic Relations of Journalistic and Media Terminology in the Persian Language - Kazem, Najlaa Ismael Mohammed (Journal of Ecohumanism, 2024)
In this research, analysed and described the journalistic and media terms in terms of semantic fields and then, mentioned the various types of relations existing between them in each field. Because in the last decade, the investigation of semantic relation between various vocabularies has attracted much interest among many linguist. The area of research is still very unexplored and there is high difficulty in analyzing semantic fields and extracting the relation between words. For this reason,this study examined . This research is divided into two parts as follows:In the first topic, analyzed the sematic relations of the journalists’ terminology as its semantic field, and the meaning of putting different terms into a semantic field and then getting the relations between the terms (synonymy, antonymy, hyponymy, incompatibility and meronymy). However, in the second topic, selected media terminology and likewise put each set of those terms in their respective semantic domain, and then defined the semantic link between one set and another. Last but not the least, the purpose of this study is to learn new terms for each field as well as to assist the journalists and media translators and Persian language learners to be familiar with these terms